2019
DOI: 10.1177/1024258919828597
|View full text |Cite
|
Sign up to set email alerts
|

The influence of collective employment relations on work accommodation: case studies in Estonia, Hungary and Poland

Abstract: Work accommodations are generally understood to refer to individual solutions for older and disabled employees that have been tailored to their specific situation within a workplace. This article, however, argues that there is potential for collective employment relations to motivate and enable social partners to develop a role in implementing reasonable accommodations and supporting older and disabled employees in the labour market. Focusing on industrial relations and work accommodation systems in Estonia, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 34 publications
(39 reference statements)
3
10
0
Order By: Relevance
“…Trade union participants in workshops had not been actively involved in negotiating workplace accommodations and neither regarded them as a matter for equal opportunities or a topic for collective bargaining (Masso et al, 2019a). The categorization of accommodations as health and safety matters is largely responsible for this, resulting in their medicalization and privatization as confidential matters between an employer and employee.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Trade union participants in workshops had not been actively involved in negotiating workplace accommodations and neither regarded them as a matter for equal opportunities or a topic for collective bargaining (Masso et al, 2019a). The categorization of accommodations as health and safety matters is largely responsible for this, resulting in their medicalization and privatization as confidential matters between an employer and employee.…”
Section: Discussionmentioning
confidence: 99%
“…The prerogative to determine how a job is conceptualized and performed has traditionally rested with the employer, but the duty on employers to make work accommodations, if properly implemented, can disrupt this both symbolically and practically. It is no coincidence, therefore, that when we reviewed the literature on industrial relations and workplace accommodations (Masso et al, 2019a) to stimulate social partner discussions in our workshops, we found that positive outcomes were most likely to be associated with a trade union presence in a workplace and representation (Bacon and Hoque, 2012;Foster and Fosh, 2010;Van Laden et al, 2015;Williams-Whitt, 2007).…”
Section: The Potential Role Of Social Partners and Industrial Relations In Developing Sustainable Work Agendas For Disabled And Older Wormentioning
confidence: 92%
See 3 more Smart Citations